Study of the effect of the formation of two-phase ceramics based on neodymium zirconate due to doping with MGO and Y2O5 on the stability of strength and thermophysical parameters under irradiation - Kozlovskiy, A.L.; Kabiyev, M.B.; Shlimas, D.I.; Uglov, V.V. (Karagandy University of the name of acad. E.A. Buketov, 2024)
The work presents the study results of the determination of the resistance of neodymium zirconate doped with MgO and Y2O5 to radiation damage stemming from irradiation with heavy ions akin to nuclear fuel fission fragments. The attraction towards this type of ceramics stems from its potential to raise the operational temperatures within the core of next-generation nuclear reactors. This is owed to its superior thermal conductivity when compared to zirconium dioxide, coupled with the heightened strength parameters that signify the ceramics' resistance against external factors. The main results of this study are to determine the influence of the formation of substitution or interstitial phases when adding magnesium and yttrium oxides to the composition, on increasing the stability of the strength and thermophysical parameters of neodymium zirconate to the radiation defects accumulation in the damaged surface layer. During the studies, it was found that the formation of impurity phases in the form of MgO inclusions (when it is added to the composition) and a substitution phase of the Y2Zr2O7 type (with the addition of Y2O5) results in an elevation in the hardness and crack resistance stability of neodymium zirconate ceramics, which indicates the positive effect of doping linked to the formation of additional interphase boundaries that prevent strain embrittlement of the damaged layer under high-dose irradiation. During determination of the thermophysical parameters of the studied neodymium zirconate ceramics, it was observed that the formation of interphase boundaries during doping not only enhances thermal conductivity but also mitigates the decline in the thermal conductivity coefficient during irradiation for two-phase ceramics in comparison with undoped neodymium zirconate ceramics.
Keywords: neodymium zirconate; doping; increasing stability; radiation defects; hardening; thermophysical parameters